How risky is it, really? : why our fears don't always match the facts - Ropeik, David (McGraw Hill-Ascent Audio, 2020)
"Clear, balanced, and lively."--Steven Pinker, bestselling author of How the Mind Works ARE YOU AFRAID OF THE "RIGHT" RISKS? Do you worry more about radiation from nuclear power or from the sun? Are you more afraid of getting cancer than heart disease? Are you safer talking on your cell phone or using a hands-free device when you drive? Do you think global warming is a serious threat to your health? GET THE FACTS BEHIND YOUR FEARS-AND DISCOVER ... HOW RISKY IS IT, REALLY? International risk expert David Ropeik takes an in-depth look at our perceptions of risk and explains the hidden factors that make us unnecessarily afraid of relatively small threats and not afraid enough of some really big ones. This read is a comprehensive, accessible, and entertaining mixture of what's been discovered about how and why we fear-too much or too little. It brings into focus the danger of The Perception Gap: when our fears don't match the facts, and we make choices that create additional risks. This book will not decide for you what is really risky and what isn't. That's up to you. HOW RISKY IS IT, REALLY? will tell you how you make those decisions. Understanding how we perceive risk is the first step toward making wiser and healthier choices for ourselves as individuals and for society as a whole. TEST YOUR OWN "RISK RESPONSE" IN DOZENS OF SELF-QUIZZES!